2008
DOI: 10.1111/j.1365-2672.2008.03865.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofhdcexpression and HDC activity by enological factors in lactic acid bacteria

Abstract: Aims:  The aim of this work was to study the influence of enological factors on the histidine decarboxylase gene (hdc) expression and on histidine decarboxylase enzyme (HDC) activity in Lactobacillus hilgardii, Pediococcus parvulus and Oenococcus oeni. Methods and Results:  Cell extracts and whole cells were used. Glucose, fructose, malic acid and citric acid diminished the hdc expression. Ethanol did not increase hdc expression or activity in cells, but increased HDC activity. Temperature and pH had effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…It was found that the histamine and tyramine concentrations were dependent on the bacterial strain, the yeast strain and the effect it has on the wine composition, the length of bacteria/yeast contact after MLF as well as the screening method used for determining the biogenic amine content. Landete et al (2008) investigated the oenological factors influencing gene expression, enzyme activity and biogenic amine production in LAB, including pH, SO 2 and ethanol.…”
Section: Amino Acidsmentioning
confidence: 99%
“…It was found that the histamine and tyramine concentrations were dependent on the bacterial strain, the yeast strain and the effect it has on the wine composition, the length of bacteria/yeast contact after MLF as well as the screening method used for determining the biogenic amine content. Landete et al (2008) investigated the oenological factors influencing gene expression, enzyme activity and biogenic amine production in LAB, including pH, SO 2 and ethanol.…”
Section: Amino Acidsmentioning
confidence: 99%
“…There are various oenological parameters that influence the decarboxylase enzyme activity as well as the biogenic amine producing ability of LAB (Landete et al 2008). Histidine decarboxylase activity is enhanced at pH 3.5 and has an optimum pH of 4.8 (Lonvaud-Funel & Joyeux, 1994).…”
Section: Biogenic Aminesmentioning
confidence: 99%
“…Factors affecting P hdcAB promoter activity and the expression of genes in the hdc cluster have been identified in several Gram-positive bacteria, like Staphylococcus capitis IFIJ12 (13), Lactobacillus saerimneri ATCC 33222, Lactobacillus sp. strain w53 (15), and L. hilgardii 464 (16,17). These include acidic pH, supplemental L-histidine, histamine, and other molecules, like glucose, fructose, malic acid, and citric acid, in the growth medium.…”
mentioning
confidence: 99%